Review of patients hospitalized due to indirect hyperbilirubinemia: A retrospective, observational study (Annals of Medical Research, 2021)
None
Keywords: Phototherapy; Indirect Hyperbilirubinemia; Exchange Transfusion; Risk Factors; Newborn.